Research and development workstation environment: the new class of Current Research Information Systems - Palagin, O.V.; Velychko, V.Yu.; Malakhov, K.S.; Shchurov, O.S. (Інститут програмних систем НАН України, 2018)
Against the backdrop of the development of modern technologies in the field of scientific research, the new class of Current Research Information Systems (CRIS) and related intelligent information technologies have arisen. It was called – Research and Development Workstation Environment (RDWE) – the comprehensive problem-oriented information systems for scientific research and development lifecycle support. The given paper describes design and development fundamentals of the RDWE class systems. The general information model of the RDWE class systems is developed. Also the paper represents the information model of the RDWE class system for supporting research in the field of ontology engineering – the automated building of applied ontology in an arbitrary domain area, scientific and technical creativity – the automated preparation of application documents for patenting inventions in Ukraine. It was called – Personal Research Information System. The main results of our work are focused on enhancing the effectiveness of the scientist’s research and development lifecycle in the arbitrary domain area.Problems in programming 2018; 2-3: 255-269